Application of the ABC methodology to reduce the delay of sales orders in a company warehouse in Barranca city - Santa Cruz Puente, Carlos Abel (2023)
Inventory management becomes more important as companies grow; therefore, it is important to improve its internal processes by seeking efficient storage methods. The processes were analyzed using problem diagnosis tools and it was observed that more than 15% of the total orders are delayed, and more than 80% are due to the fact that there is no specific location of the products in the warehouse. Under this problem, the implementation of the ABC methodology is proposed, which allowed dividing the large number of products that the company sells into families and classifying them into groups A, B and C. Subsequently, the entire company warehouse was divided into zones. Arena software was used to compare the results between the current situation and the improvement implemented. According to the results obtained, it was shown that from a reduction in picking times of 20% or more, the improvements implemented would be significant, and so it was. A reduction in picking time of approximately 33% was achieved, and late orders per day decreased on average from [5.03 ± 1.5] to [1.83 ± 0.56] orders.